Voltage Drop Study on Medium Voltage Network System at PT. Pln (Persero) UP3 Banda Aceh 20 kV Using Etap Software - Ristami, Nadia (Fidelity : Jurnal Teknik Elektro, 2025)
Distribution network systems typically begin at the GI (Main Substation) and proceed to the 20 kV feeder before being divided and sent to the ULP (Customer Service Unit). Electricity is dispersed over a considerable distance via the network, which lowers voltage and current (Voltage Drop). The length of a conductor on a medium voltage distribution channel causes this disruption, which can hurt customers by damaging electrical items. A voltage drop analysis must be performed to ascertain the amount of voltage drop along the distribution channel from the base to the end of the network in compliance with the SPLN (State Electricity Company Standard), as this disruption has a detrimental effect on customer service surpass 510% (SPLN 72: 1987). We will compare the voltage loss on the 20 kV distribution network in the Ulee Kareng feeder using simulations using etap 12.6.0 software and hand calculations utilizing formulae in this final project. Data will be collected and verified at PT. PLN (Persero) UP3 Banda Aceh prior to analysis. Current is 61.8 A and reactance is 0.164 at ULK 008-00 with a voltage of 20,000. This results in a value of 0.2317 kV and a percentage of 0.0115844%, whereas the percentage determined using etap software simulation yields a value of 0.2318 kV and a value of 1.19%. By altering the cross-sectional area, the voltage loss may be addressed because A power transformer added to a distribution with an excessive load might alter the number of turns, which will result in the channel impedance.